Inovasi Flipbook dalam Pembelajaran SMK Akuntansi: Menjawab Tantangan Teknologi dan Isu Terkini di Dunia Kerja - Serafim, Rebbeca Avrely; Dewi, Hastia Chandra Mustika; Arif, Amirul; Hakim, Luqman (FKIP Universitas Wisnuwardhana, 2025)
Innovation in accounting learning is essential to address the challenges faced by students in understanding complex material and preparing them for the world of work. This article discusses the use of flipbooks as interactive learning media in accounting education. The method used in this study is a qualitative approach with a descriptive research design. In addition, researchers also conducted direct interviews with accounting teachers at SMK Ketintang. The findings show that students who used flipbooks experienced a significant increase in understanding of accounting concepts. In addition, the flipbook also improved students' collaborative skills and facilitated the integration between theory and practice. Through digital-based flipbooks, students can learn to use appropriate accounting tools and software, so that they are better prepared to face the increasingly complex demands of the world of work. The conclusion of this study is that flipbooks are not only effective in improving learning outcomes, but also contribute to the development of skills needed in the world of work. Suggestions for future research are to explore the integration of flipbooks with practice-based projects involving businesses, in order to provide students with hands-on experience.